Non‐Ophthalmological Diagnosis of Posterior Dislocation of the Intraocular Lens - Guido Carillio; Pier Paolo Arcuri; Flora Carillio (Clinical Case Reports)
ABSTRACT In case of sudden unilateral vision loss, a detailed search for symptoms and causes is mandatory. Dislocation of the intraocular lens can occur even in the absence of trauma and sometimes is not easily detectable, but must be carefully investigated and treated.